2017
DOI: 10.1016/j.celrep.2017.02.074
|View full text |Cite
|
Sign up to set email alerts
|

The SWI/SNF Protein PBRM1 Restrains VHL-Loss-Driven Clear Cell Renal Cell Carcinoma

Abstract: SUMMARY PBRM1 is the second most commonly mutated gene after VHL in clear cell renal cell carcinoma (ccRCC). However, the biological consequences of PBRM1 mutations for kidney tumorigenesis are unknown. Here, we find that kidney-specific deletion of Vhl and Pbrm1, but not either gene alone, results in bilateral, multifocal, transplantable clear cell kidney cancers. PBRM1 loss amplified the transcriptional outputs of HIF1 and STAT3 incurred by Vhl deficiency. Analysis of mouse and human ccRCC revealed convergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
170
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(190 citation statements)
references
References 66 publications
16
170
0
4
Order By: Relevance
“…While this manuscript was under review, a manuscript was published reporting the generation of mice with targeted disruption of Vhl and Pbrm1 in the mouse kidney (60). There are several important differences between the studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this manuscript was under review, a manuscript was published reporting the generation of mice with targeted disruption of Vhl and Pbrm1 in the mouse kidney (60). There are several important differences between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are several important differences between the studies. First, Nargund et al, targeted Vhl and Pbrm1 by using the traditional Ksp-Cre driver, and the phenotype was dominated by the development of large cysts sometimes taking up half of the kidney (60). In contrast, cysts are infrequently observed in mice with targeted loss of Vhl and Pbrm1 using a Pax8 driver, and the mice survive significantly longer.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several groups have recently demonstrated the development of ccRCC in mice models upon the combined loss of Vhl and different genes; Harlander et al [20] showed that combined deletion of Vhl, p53 and Rb1 specifically in renal epithelial cells in mice caused ccRCC arising from proximal tubule epithelial cells. Nargund et al [21] demonstrated that activation of mTORC1 constituted a third driver event after loss of Vhl and Pbmr1 in their ccRCC tumour model, and Bailey et al [22] showed that Myc activation when combined with Vhl and Cdkn2a (Ink4a/Arf) deletion, produced murine kidney tumours that approximate human ccRCC. pVHL might also exert a broader role in maintaining renal integrity.…”
Section: Introductionmentioning
confidence: 99%
“…The PBAF complex suppresses the hypoxia transcriptional signature in VHL −/− ccRCC (18, 19) but its effects on tumor-immune interactions have not been thoroughly studied. To explore the potential impact of this complex on the immunophenotype of ccRCC, we analyzed previously reported whole transcriptome sequencing (RNA-seq) data from A704 ccRCC cell lines with perturbations in the PBAF complex (19).…”
mentioning
confidence: 99%